Exploring the Inclusive Praxis of Outward Bound Instructors - Robert P. Warner; Bruce Martin; Andrew M. Szolosi (MDPI AG, 2020)
Equity and inclusion are critical issues that need to be addressed in outdoor adventure education. Although some literature identifies inclusive practices for enhancing equity in outdoor adventure education, most research does not situate these practices within the contexts in which they were created and used. Therefore, the purpose of this study was to explore outdoor adventure education instructors' inclusive praxis, and the conditions that influenced their praxis on their courses and in their instructing experiences. To this end, we conducted semi-structured interviews with ten instructors from four Outward Bound schools in the USA. The instructors varied in their gender, school, types of programs facilitated, and duration of employment with Outward Bound. Our inductive analysis of the interview data focused on the identification of themes illustrating the characteristics of instructors' inclusive praxis, as well as the conditions that influenced their praxis. Themes emerged from our analysis that highlighted the macro and micro conditions that set the stage for instructors' inclusive praxis, which focused on creating spaces that fostered inclusive group cultures on their courses. The findings from this study may be a useful starting point for enhancing the instructors' role in fostering equity and inclusion on outdoor adventure education courses. We conclude with suggestions for future research.